Design and Implementation of Tree Topology in Software Defined Networking (SDN) using Mininet and OpenDaylight - Bayazid Khan, S.M; Shojib, M.M.H (International Journal of Computer Sciences and Engineering, 2021)
Software-Defined Networking is an emerging network architecture approach that enables us to control or, program the network system intelligently and centrally using software applications. This allows the user to manage the entire network consistently and holistically, regardless of the underlying network technology. By installing and configuring OpenDaylight which is a modular open platform for customizing and automating networks of any size and scale, we then configured it by Mininet in Virtual Machine. Finally, packets are captured by Wireshark and help us to measure the scenario. In this paper, our purpose is to shed light on SDN related issues and give insight into the challenges facing the future of this revolutionary network model, from both protocol and architecture perspectives. Additionally, we aim to present different existing solutions and mitigation techniques that address SDN scalability, elasticity, dependability, reliability, high availability, resiliency, security, and performance concerns.